أثر الخبرة المهنية لأساتذة التعليم الابتدائي على تسيير الزمن البيداغوجي في الأقسام متعددة المستويات (Revue El-Wahat pour les Recherches et les Etudes, 2022)
ملخص:هدفت هذه الدراسة إلى الكشف عن أثر الخبرة المهنية العامة في التعليم لأساتذة الأقسام متعددة المستويات، وتلك المكتسبة من التعليم ضمن هذه الأقسام على تسييرهم للزمن البيداغوجي، من خلال تطبيق استبيان على 145 أستاذا موزعين على ثلاث ولايات من الشرق الجزائري، في الفترة الممتدة ما بين شهري فيفري وأفريل من سنة2019 ، وباعتماد أساليب إحصائية مناسبة، لتخلص الدراسة إلى أن:- مستوى صعوبة تسيير الزمن البيداغوجي متوسط لدى أساتذة الأقسام متعددة المستويات.- لا توجد فروق بين مستويات صعوبة تسيير الزمن البيداغوجي في الأقسام متعددة المستويات تعزى للخبرة المهنية العامة في التعليم، ولا للخبرة المهنية المكتسبة من التعليم في الأقسام متعددة المستويات.  كلمات دالة: الأقسام متعددة المستويات، الزمن البيداغوجي، الخبرة المهنية، أستاذ التعليم الابتدائي.    Abstract: This study aims to reveal the impact of professional experience in education of Teachers working in Multigrade Classrooms and their experience in teaching in these classes, on the managing of study time. A questionnaire was administered to 145 teachers in three cities of the Algerian east. The study was conducted between February and April of 2019, using appropriate statistical methods to conclude that:   -The level of difficulty of managing study time is moderate for Multigrade classrooms.    -There are no differences between the levels of difficulty of managing study time of teachers due to the professional experience or to their professional experience issued in teaching in Multigrade classrooms. Keywords: Multigrade Classrooms, Study Time, Professional Experience, Primary Education Teacher.